If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -1y(2x + 2) = 22 Reorder the terms: -4x + -1y(2 + 2x) = 22 -4x + (2 * -1y + 2x * -1y) = 22 Reorder the terms: -4x + (-2xy + -2y) = 22 -4x + (-2xy + -2y) = 22 Solving -4x + -2xy + -2y = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2y' to each side of the equation. -4x + -2xy + -2y + 2y = 22 + 2y Combine like terms: -2y + 2y = 0 -4x + -2xy + 0 = 22 + 2y -4x + -2xy = 22 + 2y Reorder the terms: -22 + -4x + -2xy + -2y = 22 + 2y + -22 + -2y Reorder the terms: -22 + -4x + -2xy + -2y = 22 + -22 + 2y + -2y Combine like terms: 22 + -22 = 0 -22 + -4x + -2xy + -2y = 0 + 2y + -2y -22 + -4x + -2xy + -2y = 2y + -2y Combine like terms: 2y + -2y = 0 -22 + -4x + -2xy + -2y = 0 Factor out the Greatest Common Factor (GCF), '-2'. -2(11 + 2x + xy + y) = 0 Ignore the factor -2.Subproblem 1
Set the factor '(11 + 2x + xy + y)' equal to zero and attempt to solve: Simplifying 11 + 2x + xy + y = 0 Solving 11 + 2x + xy + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + 2x + xy + -11 + y = 0 + -11 Reorder the terms: 11 + -11 + 2x + xy + y = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 2x + xy + y = 0 + -11 2x + xy + y = 0 + -11 Combine like terms: 0 + -11 = -11 2x + xy + y = -11 Add '-1y' to each side of the equation. 2x + xy + y + -1y = -11 + -1y Combine like terms: y + -1y = 0 2x + xy + 0 = -11 + -1y 2x + xy = -11 + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4x^2+16=25 | | 8x+5-(4x)=19 | | t-9-2t=7+t | | 5x-12=6x-9 | | 8x+5-4x=19 | | 2B+3B-4=6 | | 5y-3(2y-2)=4 | | x-62=8x+8 | | -9+4n=3n | | P-6.71= | | 64t-8t^2-96=0 | | 7f-3/2*1=7 | | 75-x=87-2x | | 20x^4-30+30=0 | | y=-9(2+x) | | 5x-7=17-x | | F(x)=-x^3-2x^2+7x-10 | | 7u+9=-1+8u | | 5b-7=17+2b | | 2P=10-6(3P-2) | | 4x-9+110+35=180 | | 8c+10=7c | | -10-8r=-3r+10 | | 12+6x+60+60=180 | | 2(x+9)=x-2 | | -7x+6=-16-5x | | 4-5v+2v=16 | | -2x-5(-2x+4)=4 | | 8-4x=2x-40 | | 2(x+4)+8=16 | | 2/3(6x-9=34 | | 3q=2q-6 |